Revolutionizing Spray Drying: An In-Depth Analysis of Surface Stickiness Trends and the Role of Physicochemical Innovations in Boosting Productivity - Nik Farhan Nazmi Nik Abd Rahman; Saiful Irwan Zubairi; Haslaniza Hashim; Harisun Yaakob (Journal of Food Quality)
Spray drying is a widely utilized method in the pharmaceutical, food, and chemical industries for producing powdered products. However, a recurring challenge in this process is the persistent issue of surface stickiness, which diminishes product quality and operational efficiency. This paper examines the current trend of surface stickiness in spray drying and explores physicochemical approaches to mitigate fouling and enhance overall productivity. The stickiness is often attributed to the formation of lumps on drying chamber surfaces, adversely affecting the final product’s characteristics. The paper reviews existing literature on the causes and consequences of surface stickiness, emphasizing the need for innovative strategies to address this challenge. Promising solutions are emerging in the form of physicochemical approaches, involving the modification of drying chamber materials, applying different operational approaches, optimization of process parameters, and the introduction of drying aids. Researchers aim to alter the surface properties of drying chamber components, minimizing particle and wall deposition to prevent surface stickiness. The present review also delves into the impact of various physicochemical factors on spray drying performance, including temperature, airflow dynamics, and formulation composition. Understanding these factors is crucial for developing effective strategies to reduce fouling and enhance overall productivity in spray drying processes. This review sheds light on the prevalent issue of spray drying surface stickiness and underscores the significance of physicochemical approaches in overcoming this challenge. By addressing stickiness issues through innovative strategies, researchers and industry professionals can improve the efficiency and reliability of spray drying processes, ultimately elevating the quality of powdered products in pharmaceutical, food, and chemical manufacturing.